Thermo-Responsive Shape-Memory Effect and Surface Features in Polycarbonate (PC) - Xuelian Wu; Taoxi Wang; Weimin Huang; Yong Zhao (Applied Sciences, 2017)
The influence of programming strain and temperature on the shape memory effect and surface morphology in programmed polycarbonate (PC) samples via uni-axial stretching is investigated. It is found that the samples programmed at around the glass transition start temperature not only have micro-cracks on their surface, but also show a necking phenomenon. Furthermore, the surface of the necked area is concave, but the surface of the non-necked area is convex. On the other hand, despite the samples programmed at high temperatures being able to deform in a uniform manner at macroscopic scale, their surfaces are still uneven, either concave or convex. While the samples programmed at low temperatures are able to achieve full shape recovery, stretching at higher temperatures over the glass transition range to a higher strain may result in non-recoverable deformation.